Scrotal Calcinosis Presenting As Nodular Masses : A Report Of 4 Cases - Bhat Dharitri; Parate Sanjay; Bobhate S. K (Wolters Kluwer Medknow Publications, 2003)
Scrotal calcinosis is characterized by multiple nodular masses within the scrotal skin, slowly increasing in size. The pathogenesis is obscure and is viewed by many to be idiopathic or can result from dystrophic calcification of epidermal cysts. We report 4 cases of scrotal calcinosis presenting as multiple nodules over scrotal skin.